A utilização de fontes administrativas de dados na estimação da adesão terapêutica aos antagonistas dos recetores da angiotensina - Moita, Bruno (2018)
The recent development in electronic pharmacy records made possible the measure of patients' adherence behavior using administrative data sources. The overall objective of the study was to characterize the adherence behavior to Angiotensin Receptor Blockers of hypertensive patients living in Alentejo, Portugal, in 2010 and 2011. The results revealed that primary adherence stood at 61.2% and total adherence was situated between 55.7% and 69.5% with high variability on behavioral patterns for age, gender and geographic area.